The Effect of Aquatic and Dryland Resistance Training on Peroxisome Proliferator Activated Receptor-ɑ Gene Expression in Middle-aged Women's Peripheral Blood Mononuclear Cell after Coronary Artery Bypass Grafting - Leili Zeiaadini Dashtkhaki; Amir Rashid Lamir; Saeed Naghibi (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Cardiac rehabilitation program is aimed at reducing secondary risk factors and improving function in patients undergoing coronary artery bypass grafting run which ultimately may delay or reduce mortality in patients. A major component of cardiac rehabilitation program is exercise. Objective(s). This study is aimed at evaluating the effect of aquatic and dryland training on Peroxisome Proliferator Activated Receptor-ɑ (PPAR-α) gene expression in middle-aged women's peripheral blood mononuclear cells (PBMNCs) after coronary artery bypass grafting. Methods. Thirty middle-aged women with cardiovascular disease were categorized into three groups comprising control (CON), aquatic resistance training (ART) and dryland resistance training (DRT). The dryland training program lasted for eight weeks of resistance training (3 sessions per week/ 60 minutes per session) and included two to three sets of 12-15 repetitions with 60% of 1RM. The aquatic resistance training lasted for eight weeks (3 sessions per week/ 60 minutes per session), with 60 to 80% of 1RM for each exercise primarily. Fasting blood samples were taken from all participants 48 hours both before the beginning of the training program and after the last training session. PPARα relative gene expression was identified by Real-Time PCR method. Results. It is showed a significant increase in the relative PPARɑ gene expression in both aquatic and dryland resistance training groups (F= 15.573, P= 0.001). It is found a significant difference in aquatic and dryland resistance training groups as regards PPARɑ gene expression (P= 0.001, t= -6.954; P= 0.001, t= -5.871; respectively).  Conclusion. The results revealed that both of them on land and water training, increase PPARɑ gene expression in middle-aged women after coronary artery bypass and a possible reverse cholesterol transport process can be improved, so it is recommended that this type of training program, cardiac rehabilitation should be employed.